Republic of China on Taiwan 1991
This video explores the political, economic, social and cultural aspects of the ROC in Taiwan. It documents the innovative behavior of the ROC government and reveals the increasing pluralization of society in Taiwan. A spirit of renewal suffuses the past-paced film with the natural confidence that makes the ROC so unique.